The influence of boot stiffness on performance and quadricep muscle activity during slalom training - Seifert, J.; Park, J.; Kipp, R. (Science and Skiing VI. 6th International Congress on Science and Skiing, Dec. 14 - 19, 2013, St. Christoph am Arlberg, 2015)
The purpose of this case study was to investigate performance characteristics and integrated electromyographic (iEMG) activities from two quadriceps muscles of a national caliber ski racer while skiing in soft and stiff flex racing boots during slalom training.